Advantages of Newer Inhalational Anesthetic Agents over the Older Agents (Community Based Medical Journal, 2024)
The objective of anesthesia is to facilitate surgery at minimal risk to the patient and to ensure optimal recovery following the procedure. Sevoflurane is a potent nonexplosive newer inhalational anesthetic agent that has several advantages. Various side effects like arrhythmia, hepatotoxicity, and delayed recovery limit the use of older agent halothane in many western countries. However, we do not have such studies done in our country. This prospective study was carried out in the Department of Anesthesia, Analgesia and Intensive Care Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from September 2009 to June 2011, to analyze the advantages of newer inhalational agents over the older agents. A total of 60 patients were recruited in this study: 30 in Sevoflurane and 30 in Halothane group. We assessed hemodynamics and recovery after sevoflurane and halothane anesthesia. The mean arterial pressure (MAP) and the heart rate (HR) at 15 minutes interval were similar in both groups except at 75 minutes, when both MAP and HR were significantly higher in the halothane group as p=0.003 and p=0.001 respectively. Emergence time was 10.85 min. in the sevoflurane group and 15.13 min. in the halothane group (p